From image to insight: leveraging imaging to empower patients with inflammatory arthropathies - Chiara Conte; Chiara Conte; Anna Menegolo; Anna Menegolo; Ludovico De Stefano; Ludovico De Stefano; Serena Bugatti; Serena Bugatti; Garifallia Sakellariou; Garifallia Sakellariou (Frontiers in Medicine)
Recent advancements in the management of inflammatory arthritis have shifted the focus toward patient-centered care, with increasing emphasis on patient education, engagement, and treatment adherence. At the same time, the growing use of imaging techniques offers novel opportunities to enhance communication between healthcare professionals and patients. This review examines current evidence on how visual tools and imaging modalities can improve patient understanding, foster engagement, and strengthen adherence in inflammatory arthritis. Barriers to adherence often arise from low health literacy and entrenched beliefs about illness and medications. However, visual communication has shown promise in addressing these challenges. Research in rheumatoid arthritis (RA), juvenile idiopathic arthritis, and gout suggest that showing personal or illustrative images can increase disease insight, reinforce treatment necessity, and encourage shared decision-making. Among imaging techniques, musculoskeletal ultrasound (MSUS) stands out for its real-time use and interactive potential. Although findings—especially in RA—are encouraging, the overall evidence remains limited, with lack of research in spondyloarthritis and scarce data on long-term outcomes. Further studies are needed to develop standardized protocols and identify patient subgroups most likely to benefit. Ultimately, integrating imaging into patient education may be a valuable strategy to improve care experiences and outcomes in inflammatory arthritis.